Gastronomic Tourism Enhancement Strategy to Stimulate Local Economic Development in Malang City - Andi Normaladewi; Tri Sugiarti Ramadhan; Nanik Wahyuningtiyas (Dinasti Publisher, 2025)
The development of gastronomic tourism is an important strategy in strengthening the tourism sector and encouraging local economic growth in various regions. Malang City, as one of the leading tourist destinations in East Java, has great potential in developing its regional culinary specialties as a tourist attraction with economic and cultural value. This study aims to analyze strategies for enhancing gastronomic tourism to stimulate local economic development in Malang City, with a focus on how collaboration between stakeholders and the preservation of culinary specialties can create sustainable economic impacts. This study uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews, field observations, and document reviews from various sources, including culinary entrepreneurs, the tourism office, academics, and local communities. Data analysis was carried out using coding techniques and thematic analysis to identify strategic patterns, challenges, and opportunities in the development of gastronomic tourism in Malang City. The results show that the strategy for enhancing gastronomic tourism in Malang City focuses on three main aspects, namely: (1) strengthening local culinary identity through product innovation based on cultural wisdom; (2) cross-sector institutional collaboration with a penta-helix approach; and (3) optimizing digital promotion and culinary education for the community and tourists. This strategy has been proven not only to increase tourist visits but also create a multiplier effect on the local economy through empowering MSMEs, increasing community income, and preserving regional culinary culture. This study concludes that gastronomic tourism in Malang City has strategic potential as a driver of the creative economy and as a medium for preserving cultural identity. Collaboration between stakeholders, innovation based on local values, and inclusive public policies are key to successfully creating a competitive and sustainable gastronomic tourism ecosystem.